Thailand : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
This Selected Issues paper for Thailand highlights the effect of higher global interest rates on Thailand and the relationship between financial crises and long-term potential growth. Since the Asian crisis, Thailand has adopted an inflation targeting regime, and has intervened in the foreign exchange market to prevent excessive baht volatility. The monetary tightening in the United States in 1994 has been followed by heightened bond market volatility and a widening of emerging countries' credit spreads.